Hybrid Dynamic-Evolutionary Programming for Multi-Objective Long-Term Malaysia Generation Mix - Mariam Mohd Shokri, Siti; Yenita Dahlan, Nofri; Mohamad, Hasmaini; Nazirah Wan Md Adnan, Wan (International Journal of Engineering and Technology, 2018)
A Hybrid Dynamic-Evolutionary Programming (HDPEP) is proposed to find an optimal solution formulti-objective power generation mix model. The present contribution is intended to develop a method to facilitate simultaneous modelling of multi-objective optimization considering the cost of power generation, carbon emission and power system reliability. The study introduces the implementation of Evolutionary Programming (EP) via weighted sum method (WSM) approach within the HDPEP framework to optimize the weighted coefficient in providing accurate decision for generation mix planning. The EP-WSM reduces â€˜discriminationâ€™ when choosing the weight values of each objective function. The proposed HDPEP were compared with non-optimal weighted approach. Results show that the HDPEP model provides a better performance in providing the lowest Multi-Objectives Index (MOI)in solving multi-objective power generation mix problem. Â